Alan Ameche : The Story of "The Horse" - Manoyan, Dan (Book collections on Project MUSE., 2012)
Ameche grew up in Kenosha, Wisconsin, where he played for one of the state's best-ever high school football teams. From there he went on to break Big Ten rushing records for the University of Wisconsin Badgers, leading them to the 1953 Rose Bowl and winning the 1954 Heisman Trophy. He earned his nickname "The Horse" for his tremendous training ethic, power, and stamina. In a professional career with the Baltimore Colts that lasted just six seasons before injury ended it, he was the 1955 NFL Rookie of the Year and went to the Pro Bowl five times